Study on microwave assisted extraction of chrysophanol and its intervention in biofilm formation of Streptococcus suis. Issue 50 (17th September 2019) - Bai, Jing-Wen; Chen, Xing-Ru; Tang, Yang; Cui, Wen-Qiang; Li, Da-Long; God'spower, Bello-Onaghise; Yang, Yu
Abstract : A microwave assisted extraction technology was used to extract chrysophanol from rhubarb. Abstract : A microwave assisted extraction technology was used to extract chrysophanol from rhubarb. The present study will focus on the optimum extraction conditions of chrysophanol and discuss the inhibitory effect of chrysophanol on the biofilm formation of Streptococcus suis ( S. suis ). A Box–Behnken design based on single-factor experiments was applied to optimize the microwave assisted extraction process and to study the factors' relationships with each other. The results showed that a microwave temperature of 56 °C, ethanol concentration of 70%, microwave power of 540 W and liquid to raw material ratio of 55 mL g −1 were the optimal conditions for the microwave method. The yield of chrysophanol was 2.54 ± 0.07% under the optimal conditions, which was in agreement with the predicted value (2.64%). Then, the chemical structure of the extracted chrysophanol was identified by LC-MS. In addition, in vitro experiments showed that chrysophanol has an inhibitory effect on S. suis (minimum inhibitory concentration was 1.98 μg mL −1 ) and was shown to significantly inhibit the capability of S. suis to form a biofilm using crystal violet staining. Finally, scanning electron microscopy analysis showed that the three-dimensional structure of the biofilm deposited by the S. suis community was destroyed by chrysophanol.